Interactive Dyadic Physical Activity and Spatial Proximity Patterns in 2-Year-Olds and Their Parents - Aston K. McCullough; Helena Duch; Carol Ewing Garber (MDPI AG, 2018)
This study aimed to characterize daily physical activity (PA) behaviors in 2-year-old girls and boys and their parents, with and without an objective measure of dyadic spatial proximity. Urban-dwelling parent⁻toddler dyads (N = 110) wore accelerometers for 7 days, and parents completed a sociodemographic questionnaire. Accelerometers were initialized to collect PA and Bluetooth-based proximity data. After applying wear-time algorithms, n = 65 dyads were further analyzed using a dyadic analysis statistical methodology. Toddler⁻parent sedentary and light PA time were respectively interdependent, conditional on child sex and child-parent proximity, but moderate⁻vigorous physical activity (MVPA) time was not. Toddlers were significantly more active on weekdays and weekends than their parents, and no differences were found in daily PA volumes between girls and boys. In dyads with proximity data (n = 34), analyses of joint (i.e., proximal and mutual) PA time showed that girls participated in significantly more joint PA with their mothers than boys. Children who engaged in ≥60 min of MVPA/day participated in ~2 h of joint PA/day, on average, while children with <60 min of MVPA/day engaged in ~30 min less joint-PA time with their mothers. Boys and girls who participated in higher daily MVPA volumes engaged in joint PA with their mothers across greater relative distances, as compared to less active boys who engaged in joint PA at closer relative distances to their mothers. Toddlers who engaged in ≥60 min of daily MVPA participated in joint PA with their mothers at greater relative distances and for longer durations than less active children. Further research on the dyadic activity⁻proximity relationship is needed across early childhood development.